Effect of Antimicrobial Photodynamic Therapy on Aggregatibacter actinomycetemcomitans Biofilm using Confocal Fluorescence Imaging—An In vitro Study - R Sindhujaa; PL Ravi Shankar; K Raja Pandian; Deepak Chandrasekharan; A Sheryl Dolly; KM Mohamed Rashik (Indian Journal of Dental Research)
Introduction: Periodontitis is a significant oral health issue caused by specific microorganisms, leading to the destruction of tooth-supporting tissues. Aggressive periodontitis (AgP) is a rapidly progressing form of the disease, particularly affecting young adults. Photodynamic therapy (PDT) has emerged as a potential treatment modality for periodontitis, utilizing visible light combined with a photosensitizer to inactivate bacteria. Aim: The aim of the current in vitro study is to investigate the effect of antimicrobial photodynamic therapy on Aggregatibacter actinomycetemcomitans (A.a) biofilm using confocal fluorescence imaging. Materials and Methods: Bacterial cultures were cultured in Brain Heart Infusion broth, supplemented with horse blood, hemin, and menadione. Biofilms were inoculated into 24-well plates, treated with purpurin dye, and exposed to laser irradiation. Following treatment, biofilms were fixed, stained with a LIVE/DEAD staining kit, and examined using confocal laser scanning microscopy (CLSM) to assess bacterial viability and biofilm formation. Additionally, an MTT assay was performed to evaluate cell viability quantitatively after laser exposure. Results: Treatment groups exhibited a significant reduction in A.a viability compared to the control group. CLSM imaging revealed a decrease in viable bacterial colonies within the biofilm after PDT, with complete bacterial kill observed in some cases. Additionally, PDT resulted in alterations in biofilm structure and morphology. Conclusion: These findings demonstrate the potential of purpurin-mediated PDT as an effective antimicrobial therapy for periodontitis, offering a promising adjunct to conventional in vivo periodontal treatment approaches and has high potential in clinical applications.